Development and promotion of a national website to improve dissemination of information related to the prevention of mother-to-child HIV transmission (PMTCT) in Tanzania. (December 2015) - Stephan, Gudila; Hoyt, Mary; Storm, Deborah; Shirima, Sylvia; Matiko, Charles; Matechi, Emmanuel
Abstract Background Websites that address national public health issues provide an important mechanism to improve health education and services in resource limited countries. This article describes the development, promotion and initial evaluation of a national website to increase access to information and resources about prevention of mother-to-child transmission of HIV (PMTCT) among healthcare workers and PMTCT stakeholders in Tanzania. Methods A participatory approach, involving the Tanzania Ministry of Health and Social Welfare (MOHSW) and key PMTCT stakeholders, was used to develop and manage the online PMTCT National Resource Center (NRC), http://pmtct.or.tz/ . The website was created with a content management system software system that does not require advanced computer skills and facilitates content updates and site management. The PMTCT NRC hosts related regularly updated PMTCT-related news, resources and publications. Website implementation, access and performance were evaluated over two years using Google Analytics data about visits, page views, downloads, bounce rates and location of visitors, supplemented by anecdotal feedback. Results Following its launch in July 2013, the PMTCT NRC website received a total of 28, 400 visits, with 66, 463 page views, over 2 years; 30 % of visits were from returning visitors. During year 1, visits increased by 80 % from the first to second 6 month period and then declined slightly (9–11 %) but remained stable in Year 2. Monthly visits spiked by about 70 % during October 2013 and January 2014 in response to the release and promotion of revised national PMTCT guidelines and training manuals. The majority of visitors came from primarily urban areas in Tanzania (50 %) and from other African countries (16 %). By year 2, over one-third of visitors used mobile devices to access the site. Conclusions The successfully implemented PMTCT NRC website provides centralized, easily accessed information designed to address the needs of clinicians, educators and program partners in Tanzania. Ongoing involvement of the MOHSW and key stakeholders are essential ensure the website's growth, effectiveness and sustainability. Additional efforts are needed to expand use of the PMTCT NRC throughout the country. Future evaluations should examine the role of the website in supporting implementation of national PMTCT guidelines and services in Tanzania.